2389. Effect of Rezafungin on QT Interval in Healthy Subjects. (26th November 2018) - Flanagan, Shawn; Goodman, Daniel B; Rao, Pallavi; Jandourek, Alena; O'Reilly, Terry; Sandison, Taylor
Abstract: Background: Rezafungin (RZF), a novel, once-weekly echinocandin for treatment and prophylaxis of invasive fungal infections, successfully met safety and efficacy endpoints in Phase 2 and is advancing to Phase 3 studies. RZF is the first echinocandin to undergo a definitive QT evaluation. Methods: This Phase 1, single-center, randomized, double-blind, comparative study evaluated the effects of RZF on the QTcF (corrected using Fridericia's formula) interval), heart rate, and other cardiac parameters. There were three dose groups, RZF (600 mg or 1, 400 mg IV), IV placebo, and oral moxifloxacin (positive control). The 600 mg (therapeutic) and 1400 mg (supratherapeutic) doses were selected to achieve exposures approximating those after multiple doses of the highest dosage regimen assessed in the Phase 2 study (400 mg once weekly) and exposures 2.5-fold higher, respectively. The primary endpoint was based on an analysis of change of QTcF from Baseline (Δ QTcF) as a function of RZF plasma concentration, to derive the estimated mean placebo-adjusted change of QTcF from Baseline (ΔΔ QTcF) for the RZF dose groups at the geometric mean Cmax for each dose level. The outcome was defined by a comparison of the upper bounds of the 2-sided 90% CIs within 10 ms. Results: 60 subjects were enrolled and completed the study. Demographics included: sex (43.3% male) and age (median age 34.0 years; ranging from 20 to 51 years) approximately evenly distributed by treatment. A linear regression model best fit the data, as shown in Figure 1. From this model, the estimated mean ΔΔ QTcF at the Cmax for both of the RZF doses had upper bounds <10 ms. The mean ΔΔ QTcF at each time point by dose, showed all 1-sided 95% upper bounds to be <10 ms, thus supporting the conclusion of the primary analysis. Assay sensitivity was established for moxifloxacin. No clinically significant effects on any of the cardiac parameters tested (RR, QRS, HR) were observed. RZF was generally well tolerated. All adverse events (AE) were mild to moderate in severity with no discontinuations due to AEs. Conclusion: Rezafungin, in single IV doses up to 1, 400 mg, does not prolong the QT interval. This finding supports the clinical safety and continued development of RZF. Disclosures: S. Flanagan, Cidara Therapeutics: Employee and Shareholder, Salary and stock options. A. Jandourek, Cidara Therapeutics: Consultant, Consulting fee. T. Sandison, Cidara Therapeutics: Employee, Salary.